The solution would be like this for this specific problem:
( 3 /( 2x+5 )) + ( 21 / (8x^2 + 26x + 15))
= ( 3 /( 2x+5 )) + ( 21 / (8x^2 + 20x + 6x + 15))
= ( 3 /( 2x+5 )) + ( 21 / (4x(2x + 5) + 3(2x + 5))
= ( 3 /( 2x+5 )) + ( 21 /(2x + 5)(4x + 3)
= [ 3 (4x + 3) + 21 ] /(2x + 5)(4x + 3)
= [ 12x + 9 + 21 ] /(2x + 5)(4x + 3)
= [ 12x + 30 ] /(2x + 5)(4x + 3)
= 6(2x + 5) /(2x + 5)(4x + 3)
= 6 / (4x + 3)
I am hoping that this answer has satisfied your query and it will be able to help you in your endeavor, and if you would like, feel free to ask another question.